Cardio Vascular Autonnomic Dysfunction in Type 2 Diabetes Patients with Microalbuminuria - Syed Waqas Aslam Naqvi, Rubina Anjum, Auqib Ghulam Shah, Jawad Abbas, Salman Ahmed, Syed Ali Raza (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Main objective of this study is to determine the prevalence of cardiovascular autonomic dysfunction in type-2 diabetes patients with microalbuminuria. Study Design: Descriptive/ observational study Place and Duration: Department of Cardiology, DHQ Hospital Alpurai, Shangla, from December, 2021 to May, 2022. Methods: Total 70 patients of both genders diagnosed diabetes 2 mellitus were presented in this study. Patients were aged between 20-80 years. Patients details demographics were recorded after taking written consent. Prevalence of cardiovascular autonomic dysfunction with microalbuminuria was assessed by statistical analysis. Microalbuminuria was diagnosed among patients if urinary albumin excretion was >30-300mg/g and graded into mild, moderate and severe according to value of urinary albumin excretion was (20–50 mg/24 hr, 50–100 mg/24 hr, 100–300 mg/24 hr). Complete data was analyzed by SPSS 20.0 version. Results: Out of 70, 38 (54.3%) were males and 32 (45.7%) were females. Mean age of the patients were 49.71±17.8 years with mean BMI 28.41±9.42 kg/m2. Mean ACR of microalbuminuria was 166.7±47.8 mg/gm. Among 70 cases, mild microalbuminuria was found in 28 (40%) cases, moderate microalbuminuria was among 31 (44.3%) and 11 (15.7%) was severe microalbuminuria. Lethargy was the most common symptom found in 25 (35.7%) followed by anorexia 20 (28.6%). Frequency of Cardiac autonomic neuropathy was 58 (82.86%), Parasympathetic dysfunction found in 59 (84.3%) and sympathetic dysfunction was among 62 (88.6%). Conclusion: We concluded in this study that the cardiovascular autonomic dysfunction in type-2 diabetes patients highly associated with microalbuminuria with increased systolic diastolic pressure and heart rate. Keywords: Microalbuminuria, Type 2 Diabetes, Cardio autonomic dysfunction